Armoring Black Phosphorus Anode with Stable Metal–Organic-Framework Layer for Hybrid K-Ion Capacitors - Xu, Mengzhu; Feng, Yutong; Chen, Bingjie; Meng, Ruijin; Xia, Mengting; Gu, Feng; Yang, Donglei; Zhang, Chi; Yang, Jinhu (Nano-Micro Letters, 2021)
Potassium-ion capacitors (KICs) are promising for sustainable and eco-friendly energy storage technologies, yet their slow reaction kinetics and poor cyclability induced by large K-ion size are a major obstacle toward practical applications. Herein, by employing black phosphorus nanosheets (BPNSs) as a typical high-capacity anode material, we report that BPNS anodes armored with an ultrathin oriented-grown metal–organic-framework (MOF) interphase layer (BPNS@MOF) exhibit regulated potassium storage behavior for high-performance KICs. The MOF interphase layers as protective layer with ordered pores and high chemical/mechanical stability facilitate K ion diffusion and accommodate the volume change of electrode, beneficial for improved reaction kinetics and enhanced cyclability, as evidenced by substantial characterizations, kinetics analysis and DFT calculations. Consequently, the BPNS@MOF electrode as KIC anodes exhibits outstanding cycle performance outperforming most of the reported state-of-art KICs so far. Highlights: 1 The ultrathin metal–organic-framework (MOF) interphase layer with high mechanical/chemical stability was in situ grown on black phosphorus nanosheets (BPNSs). 2 MOF interphase layers as an ordered porous and robust protective layer can facilitate K ion diffusion and accommodate the volume change of the electrode. 3 Benefiting from the improved reaction kinetics and enhanced electrode stability, the BPNS@MOF anode for potassium-ion capacitors exhibits outstanding cycle performance.